2003
DOI: 10.1128/mcb.23.5.1623-1632.2003
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Competition Mechanism for Gene Activation In Vivo

Abstract: The mechanism by which gene regulatory proteins gain access to their DNA target sites is not known. In vitro, binding is inherently cooperative between arbitrary DNA binding proteins whose target sites are located within the same nucleosome. We refer to such competition-based cooperativity as collaborative competition. Here we show that arbitrarily chosen foreign DNA binding proteins, LexA and Tet repressor, cooperate with an adjacently binding endogenous activator protein, Gcn4, to coactivate expression of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
151
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(164 citation statements)
references
References 57 publications
12
151
0
1
Order By: Relevance
“…The observed nucleosome crowding may be the result of fully wrapped nucleosomes being transiently unwrapped and translocated, or disassembled and reassembled, by thermal fluctuations and chromatin remodeling enzymes. Alternatively, chromatin initially may have been assembled with many nucleosomes in partially wrapped states.We present a statistical mechanics framework that is in agreement with the observed crowding of genomic nucleosomes (4), as well as earlier experiments that probed differential accessibility of nucleosome-covered binding sites (11)(12)(13)(14), and studied nucleosome-induced cooperativity between DNA-binding factors (15)(16)(17). Our model attributes short interdyad distances seen in the experiment to intrinsic energetics of histone-DNA interactions.…”
supporting
confidence: 59%
“…The observed nucleosome crowding may be the result of fully wrapped nucleosomes being transiently unwrapped and translocated, or disassembled and reassembled, by thermal fluctuations and chromatin remodeling enzymes. Alternatively, chromatin initially may have been assembled with many nucleosomes in partially wrapped states.We present a statistical mechanics framework that is in agreement with the observed crowding of genomic nucleosomes (4), as well as earlier experiments that probed differential accessibility of nucleosome-covered binding sites (11)(12)(13)(14), and studied nucleosome-induced cooperativity between DNA-binding factors (15)(16)(17). Our model attributes short interdyad distances seen in the experiment to intrinsic energetics of histone-DNA interactions.…”
supporting
confidence: 59%
“…In these promoters (OPN), transcription factor binding sites are more distant from the TSS and often are located within a region that is relatively occupied by nucleosomes, compared with the NFR of low-plasticity genes. It is possible that this organization reflects a dynamic competition between nucleosomes and transcription factors for binding the promoter (Miller and Widom 2003), consistent with the high rate of histone turnover in these promoters. Furthermore, the relative distance of the binding sites from the TSS may indicate that the binding of transcription regulators is only the first step in promoter activation, requiring the subsequent transient eviction of nucleosomes from the TSSproximal regions to allow for the binding of additional regulators and/or general transcription machinery.…”
Section: Discussionmentioning
confidence: 90%
“…Most direct evidences of nucleosome-mediated cooperativity come from experimental studies that demonstrated cooperative binding of nonendogenous TFs without involvement of proteinprotein interactions and for a range of up to 200 bps (15)(16)(17). Moreover, experiments with TFs lacking activation domains have shown that synergistic activation of gene expression is determined more by the number of TFBSs than by the interactions with general TFs, polymerase, or chromatin modification machinery (31,48).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of nucleosome-mediated cooperativity has been documented by a series of in vivo and in vitro experiments (6,(15)(16)(17), which demonstrated synergistic binding and gene activation by nonendogenous TFs (e.g., Gal4 and LexA) that occupied sites on nucleosomal DNA (Fig. 1).…”
mentioning
confidence: 99%